Evolution of Composting Process in Maize Biomass Revealed by Analytical Pyrolysis (Py-GC/MS) and Pyrolysis Compound Specific Isotope Analysis (Py-CSIA) - San-Emeterio, Layla M.; López-Núñez, Rafael; González-Vila, Francisco J.; González-Pérez, José A. (Applied sciences, 2021)
An innovative approach based on the combination of analytical pyrolysis coupled with gas chromatography-mass spectrometry (Py-GC/MS) with compound-specific isotope analysis (Py-CSIA) is used to study the composting process of maize biomass. This multidisciplinary approach aims to elucidate the decomposition rate of the main biogenic materials (lignin, cellulose, proteins, lipids, and waxes) responses to the composting process. According to Py-GC/MS data/structural composition, a noticeable and significant decrease during the first stage of the composting process of carbohydrates and aromatic compounds is found, followed by a gradual increase of all compounds till the end of the experiment. This trend, along with an increase of fatty acids methyl-ester at the first composting stage, sustains the microbial activity and its stabilization over time. Py-CSIA data showed a significant enrichment in 13C in all identified compounds over time, supporting the semi-quantitative results and the decomposition of initial biomass throughout the composting process. This trend is also perceptible in lignin moieties, long-chain aliphatic structures, and isoprenoids, as highly recalcitrant compounds, presumably due to depolymerization and carbon translocation of side-chain molecules during the composting process. Compound-specific isotope values showed a good correlation with the bulk isotope data, and this served as validation of the technique. However, bulk values showed higher heterogeneity because those represent an average of all organic compounds in the sample. By combining isotopic and structural information using Py-GC/MS and Py-CSIA, we are able to provide further information and a more detailed approach to the study of the decomposition process of biomass by considering the diverse dynamics of the main biogenic compounds.